How Fatigue Is Experienced and Handled by Female Outpatients with Inflammatory Bowel Disease - Anne Beck; Palle Bager; Peter Errboe Jensen; Jens F. Dahlerup (Gastroenterology Research and Practice)
Background. Fatigue is a significant aspect of everyday life for patients with inflammatory bowel disease (IBD), and it influences their health-related quality of life. Little is known about fatigue from the patient’s perspective. Aim. To investigate how female IBD patients experience and handle fatigue. Methods. The study included 11 female outpatients. These patients were 40–59 years old and had IBD ≥ one year and a significantly increased fatigue score. Patients with severe active IBD, anaemia, comorbidity, or pregnancy were excluded. The included patients agreed to participate in a semistructured interview. The interviews were analysed using Malterud’s principles of systematic text condensation. Results. The patients described physical and mental symptoms of fatigue that led to social-, physical-, and work-related limitations with emotional consequences. To handle fatigue, the patients used planning, priority, acceptance, exercise, and support. Two of the eleven patients used exercise on a regular basis. Surprisingly, some patients indicated that they did not need to talk with professionals about their fatigue unless a cure was available. Conclusion. Fatigue in IBD includes physical and mental symptoms that limit the patients’ social-, physical-, and work-related lives. Despite this, some patients expressed that they had chosen to accept their fatigue.